2023
DOI: 10.35848/1347-4065/accbc9
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of longitudinal leaky surface acoustic waves on piezoelectric thin plates bonded to diamond substrate

Abstract: Using the finite element method, we analyzed the resonance properties of a longitudinal leaky surface acoustic wave (LLSAW) on the structure of a piezoelectric LiTaO3 (LT) or LiNbO3 (LN) thin plate bonded to a diamond support substrate. When the plate thickness was 0.3 wavelength or larger, the particle displacements of the LLSAW were substantially concentrated near the surface, and the resonance properties were significantly improved, compared to those of the single LT or LN. However, spurious responses due t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 29 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…The material Q (Q m ) of the LN was set to 600, which was determined by comparing the reported resonance properties of a Love-type SAW with FEM-based simulations. 20) From the propagation properties analysis shown in Sect. 2, the range of h/λ was divided into two regions: a non-leaky region with disappearing attenuation for the LLSAW phase velocity less than v SiC and a leaky region with a small attenuation at h/λ = 0.045 and 0.161 for the LLSAW velocity higher than v SiC .…”
Section: Simulation Of Resonance Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The material Q (Q m ) of the LN was set to 600, which was determined by comparing the reported resonance properties of a Love-type SAW with FEM-based simulations. 20) From the propagation properties analysis shown in Sect. 2, the range of h/λ was divided into two regions: a non-leaky region with disappearing attenuation for the LLSAW phase velocity less than v SiC and a leaky region with a small attenuation at h/λ = 0.045 and 0.161 for the LLSAW velocity higher than v SiC .…”
Section: Simulation Of Resonance Propertiesmentioning
confidence: 99%
“…Composite substrate structures with various combinations of materials have been studied for LLSAWs to solve the aforementioned problem. 2,[12][13][14][15][16][17][18][19][20] For instance, our research group has reported that LLSAWs with a high Q factor and electromechanical coupling factor (K 2 ) 2-3 times larger than that obtained for a single LT or LN substrate can be produced by bonding an X-cut LT or X-cut LN thin plate with a thickness of less than one wavelength λ to a high phase velocity support substrate, such as quartz, owing to the strong concentration of particle displacement in the thin plate. 12,14,[18][19][20] A high-frequency LLSAW resonator with an LN thin plate and a multilayered acoustic reflector with an SiO 2 /Pt layer has been reported at an operating frequency of 3.5 GHz.…”
Section: Introductionmentioning
confidence: 99%
“…For these reasons, compounded substrate structures that reduce propagation attenuation by combining multiple materials have been proposed and studied. [1][2][3][4][5][6][7][8][9][10][11][12] Our research group reported that the electromechanical coupling factor (K 2 ) for a bonded structure increased 2-3 times compared with that for a single substrate owing to the strong concentration effect of particle displacement on the vicinity of the surface when an X-cut LN or X-cut LT thin plate with a thickness less than 1 λ (λ: wavelength) was bonded to a quartz (Qz) support substrate with a higher phase velocity than the thin plate. 3,5,9,11) The TCF for this bonded structure (LT/quartz or LN/quartz) was better than that for single LT or LN because the thin plate with negative temperature coefficient and the support substrate with positive temperature canceled each other out.…”
mentioning
confidence: 99%